Excel and its significant contribution in the learning of accounting.Design of a didactic tool for students of the systems career of the Guayaquil University - Asencio Cristóbal, Luis (Revista Universidad de Guayaquil, 2016)
The limited use of the Excel spreadsheet in the classroom accompanied by the limited development of skills and abilities of students in the management of this software tool , are the main problems that affect learning in Accounting students of the second semester Career in Computer Engineering from the University of Guayaquil , which is why it is finding new ways to improve their teaching knowledge, skills and logical reasoning , designing formats in Excel to provide learning andtraining of future professionals . Excel is one of the most used Windows utilities today that through their knowleage and use can become the main tool for student learning Accounting. This proposal involves the creation, design and application of accounting templates, with which can significantly improve student learning, enhance their job skills enabling and increase their scholarship. Accounting in one of the subjects of the academic curriculum, which is within the administrative area of the School of Systems and its teaching has been the traditional way, i.e., through the Board and calculators, which is not consistent with the technological advancement we live in today, where you can use the computer and especially the Excel spreadsheet as a teaching resource for learning this subject.